STUDY OF THE TRAITS AND CHARACTERISTICS OF WINTER WHEAT VARIETY SAMPLES (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article discusses the study of morphologically, biologically, and economically important traits of winter wheat variety samples. During the research, the growth and development phases of winter wheat, yield components, resistance to stress factors, and characteristics important for selection were analyzed. The obtained results are of great importance for the future development of high-yielding varieties resistant to diseases and unfavorable environmental conditions.
Keywords: Winter wheat, variety sample, morphological trait, yield, selection, biological characteristic, genotype, phenotype.